Filsafat Pendidikan Anak Usia Dini Menurut Jean Piaget - Jauharotina Alfadhilah (Alzam: Journal of Islamic Early Childhood Education, 2025)
This study examines the Philosophy of Early Childhood Education According to Jean Piaget, focusing on his cognitive development theory and its application in early childhood education. Piaget argued that children construct knowledge through direct experiences, and cognitive development occurs in universal stages. In the preoperational stage, children develop symbolic abilities through language and pretend play, although they cannot think logically. Early childhood education based on Piaget's principles emphasizes concrete experiences, exploration, and activity-based learning, allowing children to construct their knowledge. Teachers act as facilitators who create learning environments that stimulate curiosity and critical thinking. The implementation of Piaget's theory in early childhood curriculum in Indonesia is relevant for creating active, creative, and constructive learning, providing a solid foundation for children's intellectual and character development.